The role of non state actors in ensuring Indigenous right to education in na era of neoliberalism: an experiential account from India - Rath, Navaneeta; Pandey, Annapurna (Universidade de Brasília, 2018)
Neo liberalism under globalisation makes an all-around attack against state intervention and promotes privatisation. Contrary to it, rising consciousness for inclusion and protection of human rights demands ensuring opportunities to all by increasing access, equality and quality. Education is a basic human right. But inclusive education in India is still a myth. Odisha , a constituent state of Indian federalism and housing 62 tribes has witnessed its limitations in universalising education at a micro level, particularly in the interior physically delinked tribal areas. Under such a situation, the non state actors have come forward to substitute and to supplement the state action. The present paper by adopting an exploratory design and resorting to qualitative method has tried to document the empirical experiences gained from the field on the effective innovations launched by a CSO. The objective of the paper is to indicate the efficacy of non state actors through CSO induced innovations experimented in the sample schools under empirical study, its adaptation by the local milieu and impact on the indigenous right to education. The paper concludes that the non state actors have come up in a great way to fill up the vacuum created by the withdrawal of state and are going to play a significant role in the governance of the flagship programmes and giving a fillip to the constitutional mandates.